Subjective status and perceived legitimacy across countries. (30th June 2020) - Brandt, Mark J.; Kuppens, Toon; Spears, Russell; Andrighetto, Luca; Autin, Frederique; Babincak, Peter; Badea, Constantina; Bae, Jaechang; Batruch, Anatolia; Becker, Julia C.; Bocian, Konrad; Bodroža, Bojana; et al.
Abstract: The relationships between subjective status and perceived legitimacy are important for understanding the extent to which people with low status are complicit in their oppression. We use novel data from 66 samples and 30 countries ( N  = 12, 788) and find that people with higher status see the social system as more legitimate than those with lower status, but there is variation across people and countries. The association between subjective status and perceived legitimacy was never negative at any levels of eight moderator variables, although the positive association was sometimes reduced. Although not always consistent with hypotheses, group identification, self‐esteem, and beliefs in social mobility were all associated with perceived legitimacy among people who have low subjective status. These findings enrich our understanding of the relationship between social status and legitimacy.